A spectroscopic investigation of aziridines and natural products occuring in Salsola tuberculatiformis Botsch. - Schultz, Heinrich W.(Heinrich Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.